Subsidiarily in her/his own sphere. Women and Christian politics - Wearne, Bruce C. (Koers, 1999)
This article is a discussion of the attitude of Christian social thought to women. In 1891 two influential Christian documents addressed this issue. Pope Leo XW's Rerum Novarum and Abraham Kuyper’s Het sociaale vraagstuk der Christelijke religie were responses to industrialization and subsequent Christian responses to feminism have had to face the legal, cultural and political aspects of the enhanced female participation in commerce which assumes equality for all consumers in the market-place. Catholic and Protestant political initiatives in Europe in the early 20th century, in line with these two approaches, assumed that the vocation of Christian women, inside and outside the domestic sphere, has to be that of a bulwark against materialism and liberalism. In line with this point o f view they helped to counter the domination of market-place values over all spheres of social life. These documents are also part o f latter-day efforts to reconsider women’s place. Female involvement in industry and public life around the world increases unabated as "affirmative action ” re-structures the public status of women. The ambiguous legacy o f "economic rationalism " poses new threats since the burden of social welfare falls again onto the shoulders of overworked women. A sociological account which would be Christian must address historical, social and economic ambiguities. This article explores the issue, noting typical ways in which these two prominent Christian contributions will be interpreted.